An unusual ocular complication following dental anaesthesia: case report. (September 2016) - Kempster, C; Ghabriel, M; Kaidonis, G; Townsend, G
Abstract: Used routinely by dental practitioners, local anaesthetics are generally a safe and effective means of achieving pain control during invasive dental procedures. Delivery, however, is technique sensitive and the potential for patient complication exists. Although reasonably rare, ocular complications have occurred, often leaving the patient and the clinician in distress. Such reported events have almost always involved tissue responses ipsilateral to the injection site. The current case report presents an unusual event involving involuntary fasciculation or hemifacial spasm and eventual eyelid closure on the contralateral side following a routine inferior alveolar nerve block. Aspects including the patient's history, the observed response, a pathophysiological hypothesis and patient management are discussed.